2007
DOI: 10.1007/s10661-007-9629-y
|View full text |Cite
|
Sign up to set email alerts
|

The early warning of aquatic organophosphorus pesticide contamination by on-line monitoring behavioral changes of Daphnia magna

Abstract: In this paper, the movement behavior of Daphnia magna was studied as a bio-indicator of organophosphorous pesticide (OP) contamination, using an on-line bio-monitoring method, the Multispecies Freshwater Biomonitor®. A static test of acute toxicity test revealed the 24-h and 48-h LC 50 values (95% confidence limit) for Daphnia magna to be respectively 0.45 μg/l and 0.21 μg/l for dipterex 3.80 μg/l and 0.90 μg/l for malathion, and 1.25 μg/l and 0.38 μg/l for parathion. The behavior strength of Daphnia magna was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
79
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 28 publications
4
79
0
1
Order By: Relevance
“…recent studies have focused on other sub-lethal endpoints. Some researchers found that reproduction of D. magna was affected by its exposure to direagents and atrazine, and that the exercise capacity of D. magna was inhibited by organophosphorus pesticides and carbamate pesticides through inhibiting cholinesterase (Dodson et al 1999, Barata et al 2004, Ren et al 2007). However various contaminants could affect the enzyme activities differently in D. magna.…”
Section: Introductionmentioning
confidence: 99%
“…recent studies have focused on other sub-lethal endpoints. Some researchers found that reproduction of D. magna was affected by its exposure to direagents and atrazine, and that the exercise capacity of D. magna was inhibited by organophosphorus pesticides and carbamate pesticides through inhibiting cholinesterase (Dodson et al 1999, Barata et al 2004, Ren et al 2007). However various contaminants could affect the enzyme activities differently in D. magna.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral responses in organisms associated with stress and toxicant exposure provide novel information including short term and median lethal exposure effects, and the potential for mortality (Andrew et al, 2004;Ren et al, 2007), which cannot be gained from traditional toxicological methods. Therefore, in the biological early warning of accidental water environment pollution, the on-line monitoring of the behavioral responses of aquatic organisms is viable (Ren et al, , 2009a(Ren et al, , 2009b.…”
Section: Introductionmentioning
confidence: 99%
“…magna and Japanese madaka (Oryzias latipes) were often used as the representative of water fleas and fish in the on-line biomonitoring systems, e.g., DaphniaToximeter, MFB, and BEWs. The freshwater cladoceran D. magna Straus are normally considered as sensitive to contaminants (Sturm and Hansen, 1999;Rosa et al, 2006;Ren et al, 2007). This species has often been used in bioassays and environmental monitoring of aquatic systems due to the ease and economy of maintaining cultures (Tomasik and Warren, 1996;Martínez-Jerónimo et al, 2005;Heckmann et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T, P, and M meant the effects of trichlorfon, parathion, and malathion separately on medaka BR toxic effect. In 5 TU OP treatments during the exposure period, medaka BR met a great many changes, which mainly included stimulation, acclimation, adjustment (readjustment), and toxic effect [37]. In the highest concentration exposure, it was hard for medaka to have the capability of adjustment.…”
Section: Persistence Modelmentioning
confidence: 99%